Sufistic Literature and The Spiritual Anxiety of Modern Man: A Hermeneutic Reading of Meditation Poems By Abdul Hadi W.M. - Hanif Abdulloh; Mubarokah Wasilatul (Civiliza Publishing, 2025)
Literature serves not only as a medium of aesthetic expression, but also as a space of transcendental experience that allows humans to experience and reflect on their relationship with the Divine. This article examines the “Meditasi” poem by Abdul Hadi W.M. as a representation of sufistic literature in the context of modern Indonesian literature. This research aims to uncover how poetry presents a spiritual experience through symbols, imagination, and poetic language that is visionary. The approach used is Henry Corbin's sufistic hermeneutics, especially the concept of imaginalist mundus (the imaginary realm), as well as Rudolf Otto's religious phenomenology of numinous experience as mysterium tremendum et fascinans. The results of the analysis show that “Meditasi” poetry constructs a symbolic space that cannot be reduced to a mere rational allegory, but rather represents the spiritual reality experienced existentially. Symbols such as light, birds, holy cities, lions, worms, and the sacrament of nothingness serve as imaginary images that present mortal experience, ontological mortality, and the search for divine essence. This poem displays the tension between the search for God in formal religious institutions and the discovery of God as an inner reality that resides in man. Thus, “Meditasi” shows that literature can be an effective contemplative medium in responding to the spiritual anxieties of modern man. Poetry is not merely an aesthetic text, but a space of religious experience that connects the empirical world with a transcendental dimension. This research confirms Abdul Hadi W.M.'s position as a modern Sufi poet who continues the tradition of Sufistic literature in the context of contemporary Indonesian culture.